1α,25-Dihydroxyvitamin D(3) and its analog, 2-methylene-19-nor-(20S)-1α,25-dihydroxyvitamin D(3) (2MD), suppress intraocular pressure in non-human primates - Kutuzova, Galina D. (2011)
Ocular hypertension is the greatest known risk factor for glaucoma that affects an estimated 70 million people worldwide. Lowering intraocular pressure (IOP) remains the mainstay of therapy in the management of glaucoma. By means of microarray analysis, we have discovered that 1α,25-dihydroxyvitamin D(3) (1,25-(OH)(2)D(3)) regulates genes that are known to be involved in the determination of intraocular pressure (IOP). Topical administration of 1,25-(OH)(2)D(3) or its analog, 2-methylene-19-nor-(20S)-1α,25-dihydroxyvitamin D(3) (2MD), markedly reduce IOP in non-human primates. The reduction in IOP is not the result of reduced aqueous humor formation, while a 35% increase in aqueous humor removal by 1,25(OH)(2)D(3) was found but this increase did not achieve significance. Nevertheless, our results suggest that 1,25-(OH)(2)D(3) or an analog thereof may present a new approach to the treatment of glaucoma.